(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Bangladesh is a pharmemerging country due to its large population. The pharmaceutical industry is one of the priority industries for revenue earning of the government of Bangladesh, and the industry contributes 1.0% of the gross domestic product of the country. The industry value was TK 265.95 billion in MAT 2Q, 2022. The IMS provides pharma industry value based on estimation, but it may differ from the true industry value. The study presents the pharma industry size in Bangladesh and evaluates the difference between the IMS and the true market value of the industry by an appropriate statistical test. The study collects 12 quarters, QTR 3Q, 2019 to QTR 2Q, 2022, sales data of ACI, one of the leading manufacturers, from both IMS and the company. The study finds, on average, quarterly, there is a 23.8% sales difference between the true sales value and IMS sales value in Bangladesh. The study chooses the Mann-Whitney-Wilcoxon U (MWWU) test to evaluate the difference between the IMS sales value and the true sales value of a company. The difference between the IMS sales value and the true sales value is statistically significant as the P of the MWWU test is 0.0001743 < 0.01. The limitation of this study is drawing a sales gap issue based on the analysis of a company. For a more meaningful conclusion, further study is required involving others manufacturers. However, This study might be helpful for different national and international bodies such as industry practitioners, researchers, and other stakeholders interested in entering the pharma industry of Bangladesh for business, research, or other purposes.